Assessment of Climate Change induced Household Vulnerability in Nepal: Application of Index Method - Raghu Bir Bista (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
This study examines the relationship between the magnitude of climate variability and household vulnerability in the catchment areas of Sot Khola sub-water basin in the western mountainous Surkhet, Nepal by constructing a theoretical climate vulnerability index based on household-level data collected from 642 Household covering adaptive, sensitive, and exposure. Its result is the climate vulnerability index (CVI) of households living in Sot Khola sub water basin’s catchment areas, which provides sufficient evidence of heterogeneity in climate variability and vulnerability of households across location and altitude of the catchment areas. In all clusters, all households are vulnerable at a different level. Households have the heterogeneous adaptive capacity in which about 40 percent of households have less adaptive capacity indicating potentially vulnerable households, although 60 percent of households have higher adaptive capacity. The majority of households (52.7%) are sensitive to Climate-induced disasters: landslides and floods due to their socio-economic status and food insufficiency. But about 47.4 percent of households are less sensitive. Since households’ locations are far from flood and landslides patches, about 4.4 percent of households are higher exposure but 95.6 percent of households are in less exposure. The composite index of climate vulnerability index shows 50 percent moderate and higher vulnerable household from climate-induced disaster: landslide and flood. It was supplemented by additional 17.0 percent moderately vulnerable households. Thus, in total, about 67 percent of household is vulnerable at a different level from moderate to extremely higher vulnerable. The remaining (33 percent) is least vulnerable.